MODERN ASPECTS OF TREATMENT OF WOMEN WITH POLYCYSTIC OVARY SYNDROME - Semenyna , Halyna; Fartushok , Tetiana; Zhurak , Olesia; Turok , Viktoria (Collection of scientific papers «ΛΌГOΣ», 2023)
Polycystic ovary syndrome (PCOS) is one of the most common neuroendocrine syndromes of reproductive age, affecting up to 20% of women in this age group. This condition is characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovary morphology. In the pathophysiology of PCOS, there is a violation of the circadian rhythm of GnRH secretion, which increases the release of LH and decreases FSH. The latter is necessary for the synthesis of aromatases, which convert androgens into estrogens [7]. Another pathophysiological link in the development of PCOS is insulin resistance. Androgen hypersecretion increases the level of insulin resistance, and the hyperinsulinemia that develops due to insulin resistance further increases androgen secretion and induces the production of sex hormone-binding globulin (SHBG) in the liver, thereby increasing the concentration of free testosterone in the blood and even more aggravates disorders associated with hyperandrogenism. In 2003, a consensus of experts at a joint ESHRE/ASRM symposium in Rotterdam adopted diagnostic criteria (remaining relevant to this day), which include a triad of signs: oligoovulation or anovulation; hyperandrogenism (clinical and/or biochemical manifestations); polycystic ovaries detected during ultrasound; diagnosed on the basis of at least two of the following signs [7]. Patients may have different manifestations of this triad depending on the disease phenotype, patient age, and lifestyle. Therefore, treatment strategies are symptomatic and depend on desired goals and clinical preferences.